Az erdőgazdálkodás területfejlesztési hatásai, avagy a soproni közeg turisztikai alakulása az erdő, mint természeti kincs befogadásával - Határ Melinda Nikoletta (2016)
The thesis examines the effects of forest management in a dominant touristic destination called Sopron. The effects on two different fields are especially important: tourism and life of local population. How can they profit from the natural capabilities’ possibilities in their own business? The development possibilities must be find which are able to produce the most successful outcomes from the aspect of the city’s touristic potential. Those factors must be reduced which could determine a negative shift in the city’s current or future development. The aim is to utilize the possibilities of the forests and forest management and to introduce them into the every days of the touristic units. I try to find the ways based on the gained information of the research which allow that the forests could gather ground (involvement into service, improvement of the city’s reputation, boosting up the economy life). I use the opinions of such actors in the local economy who have a good perspective onto the relationship of tourism and forest management. I formulate the ways of the possibilities’ utilization and I analyze the needed resources and the further future.